Delaying first pregnancy in reducing burden of unintended pregnancy among married adolescents in urban slums of Bangladesh - Fauzia Akhter Huda; Anisuddin Ahmed; Hassan R. Mahmood; Faisal Ahmmed; Alessio Panza; Ratana Somrongthong (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The purpose of this paper is to assess the effect of delaying first pregnancy in reducing burden of unintended pregnancy (UP) among married adolescent girls in urban slums of Bangladesh. Design/methodology/approach - This cross-sectional survey was conducted among 783 married adolescents in five urban slums of Bangladesh during January 2013-January 2014. Findings - Half of the respondents' first pregnancy was reported as unintended. Of the respondents, 58 percent with no school education had experienced UP which was 38 percent among respondents with eight year's education. Respondents who did not willingly agreed to their marriage experienced more UP (61 percent) than those who were agreed/got married by their own choice (51 percent). Respondents having five years of age difference with their husbands experienced more UP (58 percent) than those with ten years of age difference (46 percent). Respondents aged 14 years at first conception experienced 63 percent UP, while the respondents aged 18 years had 35 percent UP experience. Of the respondents, 66 percent who became pregnant within one year of marriage reported their pregnancy as unintended which was 29 percent among those who delayed their first pregnancy for three years. Originality/value - Significant association was observed between pregnancy intention with respondents' educational status (p=0.03), age difference with husbands (p=0.02), age at first conception (p<0.01) and delaying first pregnancy (p<0.001).